Pediatrician Tactics In The Treatment Of Acute Gastroenteritis In Children (Texas Journal of Medical Science, 2024)
The high frequency of acute intestinal infections in children, most of which occur in young patients, determines the need to develop modern recommendations for their diagnosis and treatment. This article provides data on the etiology of intestinal infections, as well as the results of research by domestic and European scientists regarding the effectiveness of treatment of acute gastroenteritis, including information on the use of sorbents, probiotics, antiemetic and antibacterial drugs.